The Use of a Serious Game to Assess Inhibition Mechanisms in Children - Crepaldi, Maura; Colombo, Vera; Mottura, Stefano; Baldassini, Davide; Sacco, Marco; Cancer, Alice; Antonietti, Alessandro (Frontiers in Computer Science, 2020)
The design and implementation of a serious game (SG) concerning inhibition skills in children are presented. The SG consists of a set of activities, each eliciting the tendency to respond in an immediate and inappropriate (wrong) way. The SG is based on the Dual Pathway Model of ADHD proposed by Sonuga-Barke and on the Unity/Diversity model of executive functions proposed by Miyake. In the SG children must block impulsive tendencies, reflect upon the situation, inhibit irrelevant thoughts and find the non-immediate solution. A study was carried out by testing the SG on typically developing primary school children (30 children, 16 boys; age: M = 9.30 yrs., SD = 0.87) to verify that it measures the same variables addressed by tests usually employed to assess attention ability in children and to diagnose ADHD. Three standardized tasks belonging to the Italian Battery for ADHD were administered, as well as an ad hoc questionnaire devised to check the acceptability, usability and comprehensibility of the SG. Positive correlations between impulsiveness as measured by standard tests and impulsiveness scores in the SG emerged. These findings support the notion that skills associated with the control of impulsivity are involved in the SG. Furthermore, self-report ratings in the questionnaire showed that the SG is easy to be understood, is engaging and elicits positive reactions in children.